Socs3a is Dispensable for Zebrafish Hematopoiesis and is Required for Neuromast Formation - Mohamed Luban Sobah; Clifford Liongue; Alister C. Ward (Frontiers in Bioscience-Landmark)
Background: Suppressor of cytokine signaling (SOCS)3 is a regulatory protein that participates in an important negative feedback loop downstream of several critical cytokines, especially members of the interleukin-6 (IL-6) family. As a result, SOCS3 has been shown to impact the development and function of blood and immune cells. Zebrafish harbor duplicates of SOCS3, Socs3a and Socs3b, both of which possess conserved functional domains. Methods: This study explored the role of zebrafish Socs3a by creating a whole genome knockout using CRISPR/Cas9, with a focus on hematopoiesis and neuromast formation. Results: A zebrafish Socs3a knockout mutant was successfully generated. Characterization of this mutant revealed that normal hematopoiesis was not impacted nor was neutrophils lacking Socs3a displayed normal responses to injury or their production during emergency granulopoiesis. Neuromast formation was severely impacted in Socs3a knockout zebrafish. Conclusions: Zebrafish Socs3a mutants display normal hematopoiesis and myeloid function, but the formation of the lateral line neuromast was affected by the absence of Socs3a.